Assessment of food manufacturing and hygienic practices and compliance of tupig production in Villasis, Pangasinan - Mendoza, Carlos John Benedict C. (College of Home Economics, University of the Philippines Diliman, 2023)
Tupig is a traditional rice cake wrapped in banana leaves and grilled over charcoal, with ground glutinous rice, coconut strips, and sugar as its main ingredients. It is sold throughout northwestern Luzon, although variations in the formulation, processing, production, and adherence to existing food laws are present among manufacturers within the region. Existing manufacturing and hygienic practices and compliance with local food regulations of Tupig manufacturers (n=5) in Villasis, Pangasinan was evaluated remotely through qualitative and quantitative approach using a self-administered questionnaire. Main raw materials used by the participants were ground glutinous rice and coconut meat, while the cooking method employed was charcoal grilling. Other ingredients such as margarine and butter were used for flavor enhancement. Systems for purchasing, storage and usage fall under Just-in-Time (JIT) inventory method, with inspection being done through visual and odor examination and checking of expiration dates. Cooking temperature and time was dependent on the amount of batter to be cooked, while the indicator of doneness was based on the resulting color. Only 40% of the respondents were able to attend Food Safety Training within the last 3 years, while 60% were able to secure sanitary permits, exhibiting partial compliance. Strict compliance was observed in almost all aspects (excluding going to work while sick) on Personal Hygiene. Respondents also showed strict compliance under Cross Contamination Prevention and Sanitation regarding aspects of work area cleanliness, utensils sanitation, glove changing, and use of protective cap and clothing. Strict compliance was also observed under Food Preparation in areas concerning segregation and separation of cooked and RTE foods, proper storage conditions and storage labeling, and inspection of raw materials and expiration dates. Further assessment and verification is needed to confirm whether survey results are observed onsite. Areas for improvement include compliance with food safety training requirements, proper decorum/behavior during food preparation, proper use of PPE and appropriate product labels.